2011
DOI: 10.1037/a0024292
|View full text |Cite
|
Sign up to set email alerts
|

The past makes the present meaningful: Nostalgia as an existential resource.

Abstract: The present research tested the proposition that nostalgia serves an existential function by bolstering a sense of meaning in life. Study 1 found that nostalgia was positively associated with a sense of meaning in life. Study 2 experimentally demonstrated that nostalgia increases a sense of meaning in life. In both studies, the link between nostalgia and increased meaning in life was mediated by feelings of social connectedness. Study 3 evidenced that threatened meaning increases nostalgia. Study 4 illustrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
450
1
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 370 publications
(482 citation statements)
references
References 100 publications
23
450
1
8
Order By: Relevance
“…Previous research suggests that music is a powerful source of nostalgia and music/song lyrics have been reliably used to evoke nostalgia in previous studies (e.g., Barrett et al, 2010;Routledge et al, 2011).…”
Section: Methodsmentioning
confidence: 96%
“…Previous research suggests that music is a powerful source of nostalgia and music/song lyrics have been reliably used to evoke nostalgia in previous studies (e.g., Barrett et al, 2010;Routledge et al, 2011).…”
Section: Methodsmentioning
confidence: 96%
“…This literature documents that nostalgia increases perceived meaning in life (Routledge et al, 2011).…”
Section: Implications and Future Research Directionsmentioning
confidence: 99%
“…Based on literature that nostalgia contributes to a sense of meaningfulness (Juhl et al, 2010;Routledge et al, 2011;Routledge, Wildschut, Sedikides, & Juhl, in press), we hypothesized and tested in a single study that individuals who feel highly (vs. little) bored would become more nostalgic, and, in turn, would experience increased sense of meaningfulness. Prior work has shown that a momentary sense of meaningfulness contributes to more general perceptions of presence of meaning in one's life (Van Tilburg & Igou, 2011b).…”
Section: Study 6: Boredom Re-establishes Meaningfulness Through Nostamentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to existential threat, Routledge et al (2011) found that recalling a nostalgic (relative to a neutral) event increased subjective vitality, particularly for participants who perceived life as meaningless (compared to meaningful).…”
Section: Organizational Nostalgia Increases Work Meaning When Burnoutmentioning
confidence: 99%